Psikologi Manajemen sebagai Penggerak Inovasi Budaya Organisasi dalam Meningkatkan Efektivitas dan Profitabilitas - Sofyan Sauri; Ulfia Rhodhotul Jannah; Iqbal Alfan Ni’amulloh; Mu’alimin Mu’alimind (CV. ITTC INDONESIA, 2026)
The development of modern organizations demands continuous innovation to maintain effective performance and competitiveness. In this context, the human factor is a crucial element determining organizational success. Management psychology presents itself as an approach that integrates psychological principles with management practices to understand individual behavior within organizations, such as motivation, communication, leadership, and group dynamics. However, various previous studies still tend to discuss psychological aspects partially and have not comprehensively examined the relationship between management psychology, organizational culture innovation, and their impact on organizational effectiveness and profitability. Therefore, this study aims to analyze and synthesize various literature studies on the role of management psychology as a driver of organizational culture innovation in improving organizational effectiveness and performance. This study uses a literature review method by searching for scientific articles through the Google Scholar database with the help of the Publish or Perish application. The keywords used are